Employment in Europe 1997. (Employment and social affairs, 1997)
Summary: The 1997 "Employment in Europe" points out the recent developments in jobs and employability, the flexibility in working patterns, in wages and salaries, the geographical and occupational mobility, an employment agenda for the year 2000. It also gives details for the trends and prospects in employment and unemployment in EU, the short-term prospects, the pattern of employment change in part-time and full-time jobs, the demographic trends and prospective changes in the Union's labour force, the migration, regional migration, commuting, variations in regional labour costs, the employment in services, the employment situation of people with disabilities.